2011
DOI: 10.3892/or.2011.1150
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia enhances the invasive and migratory activity of pancreatic cancer cells via hydrogen peroxide

Abstract: Abstract. Diabetes mellitus and pancreatic cancer are intimately related. Hyperglycemia, a chronic abnomality in diabetes, has been proved to be an independent predictor of mortality from cancer of the pancreas. However, little is known regarding the effect of hyperglycemia on pancreatic cancer cells. The aim of the present study was to evaluate whether increases in glucose concentration modulate the invasive and migratory potential of cancer cells, contributing to their enhanced metastatic behavior. Human pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…In our study, we investigated cellular invasion and the role of HO-1 using a Transwell chamber, and the results demonstrated that HG enhanced the capacity of A549 cell invasiveness. Similar studies have been described in A549 cells, pancreatic cancer cells and a human breast cancer cell line [12,59,60]. This finding was also supported by the report that HG levels contribute to tumor formation and progression in A549 cells [7] However, this invasiveness potential was deterred by HO-1 knockdown, which suggested that the HG-enhanced invasiveness potential was mediated by HO-1.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, we investigated cellular invasion and the role of HO-1 using a Transwell chamber, and the results demonstrated that HG enhanced the capacity of A549 cell invasiveness. Similar studies have been described in A549 cells, pancreatic cancer cells and a human breast cancer cell line [12,59,60]. This finding was also supported by the report that HG levels contribute to tumor formation and progression in A549 cells [7] However, this invasiveness potential was deterred by HO-1 knockdown, which suggested that the HG-enhanced invasiveness potential was mediated by HO-1.…”
Section: Discussionsupporting
confidence: 77%
“…Several lines of evidence have indicated that HG enhances the invasiveness potential of MCF-7 breast cancer cells [44,59] and of pancreatic cancer cells [45,60]. Furthermore, previous studies have indicated that HO-1 positively correlates with tumor stage and lymph node metastasis and that HO-1 is associated with NSCLC progression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little attention has been focused on the role of hyperglycemia in inducing the cancer cell EMT phenotype. Our results demonstrated that high glucose could increase the production of ROS in the PC cell lines BxPC-3 and Panc-1, which further leads to cell motility and invasiveness [86]. We hypothesized that hyperglycemia facilitates PC metastasis by EMT induction and vascular destruction via oxidative stress [87].…”
Section: Hyperglycemia and Cancer Cell Metastasismentioning
confidence: 99%
“…Hyperglycemia is associated with increased reactive oxygen species production and oxidative stress, which may be involved in the pathogenesis and invasiveness of pancreatic cancer. [810,27] Insulin resistance-related hyperinsulinemia might increase cancer progression by increasing cell proliferation, decreasing apoptosis, and enhancing cell responsiveness to other growth factors such as insulin-like growth factor. [19,28,29] Diabetes might alter the regulation of hormones such as adiponectin and leptin, which in turn leads to cancer growth via multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%